Analysis and design of 4-bit magnitude comparator - Aung Thura (2008)
This project involves the analysis and design of 4-bit Magnitude Comparator. This chip is available commercially as SN5485, SN54L85, SN54LS85, SN54S85 or SN7485, SN74L85, SN74LS85, SN74S85. The Data sheet is obtained and attached in Appendix A.